Cerebellar Intermittent Theta-Burst Stimulation Reduces Upper Limb Spasticity After Subacute Stroke: A Randomized Controlled Trial - Chen, Yi; Wei, Qing-Chuan; Zhang, Ming-Zhi; Xie, Yun-Juan; Liao, Ling-Yi; Tan, Hui-Xin; Guo, Qi-Fan; Gao, Qiang (Frontiers in Neural Circuits, 2021)
Objective: To explore the efficacy of cerebellar intermittent theta-burst stimulation (iTBS) on upper limb spasticity in subacute stroke patients. Methods: A total of thirty-two patients with upper limb spasticity were enrolled and randomly assigned to treatment with cerebellar iTBS or sham stimulation before conventional physical therapy daily for 2 weeks. The primary outcomes included the modified Ashworth scale (MAS), the modified Tardieu scale (MTS), and the shear wave velocity (SWV). The secondary outcomes were the H-maximum wave/M-maximum wave amplitude ratio (H max/M max ratio), motor-evoked potential (MEP) latency and amplitude, central motor conduction time (CMCT), and the Barthel Index (BI). All outcomes were evaluated at baseline and after 10 sessions of intervention. Results: After the intervention, both groups showed significant improvements in the MAS, MTS, SWV, and BI. In addition, patients treated with cerebellar iTBS had a significant increase in MEP amplitude, and patients treated with sham stimulation had a significant decrease in H max/M max ratio. Compared to the sham stimulation group, the MAS, MTS, and SWV decreased more in the cerebellar iTBS group. Conclusions: Cerebellar iTBS is a promising adjuvant tool to reinforce the therapeutic effect of conventional physical therapy in upper limb spasticity management after subacute stroke (Chinese Clinical Trial Registry: ChiCTR1900026516).